RnD & ADDIE IN DESIGNING AND DEVELOP A MOBILE-BASED FOOD ORDERING AND PAYMENT INFORMATION SYSTEM - Agustin, Siti Amalia; Al-Qasri, M Fariq; Jayani, Lulu Mitra (Universitas Islam Negeri Raden Intan Lampung, 2024)
The development of a food ordering and payment information system using MIT App Inventor addresses the need for efficient and convenient solutions in the restaurant industry. This study utilized the Research and Development (RnD) method, incorporating the ADDIE procedure and the MIT framework to design and implement the system. The major findings indicate a significant improvement in operational efficiency, service quality, data security, and customer convenience. By enabling online ordering and payment processing, the system streamlines restaurant operations and enhances the overall customer experience. The secure storage of sales and order data minimizes the risk of data loss and fraudulent activities, ensuring reliable transactions. Furthermore, the system's ability to prevent fictitious orders and provide customers with a user-friendly platform for menu browsing and payment contributes to a more efficient and secure dining experience. The discussion highlights the implications of these findings, emphasizing the system's potential to revolutionize traditional restaurant transactions and improve service delivery. Suggestions for further refinement include additional testing, integration with POS systems, user training, feedback mechanisms, security enhancements, and market expansion. By implementing these suggestions, the food ordering and payment system can maximize its impact on the restaurant industry, leading to enhanced operational efficiency and customer satisfaction.